Effect of Continuous Lateral Rotation Therapy Vs Manual Lateral Positioning on Bed Sore For Prolonged Bed Ridden Patients - Yadav, Ankita; Patil, Pragati (Journal of Neonatal Surgery, 2025)
Introduction- Pressure ulcers are common among prolonged bedridden patients and can result in pain, anxiety, and extended hospital admissions. This study examines two strategies for preventing and treating pressure ulcers: Continuous Lateral Rotation Therapy (CLRT) and manual lateral positioning. CLRT employs a specific bed to rotate the patient to relieve pressure, whereas manual positioning requires caregivers to turn the patient on a regular basis. Both strategies aim to lower the risk of pressure ulcers while also improving patient comfort and health. This study examines the effectiveness of these treatments to determine the best way to care for people who are unable to walk independently. Objective-1] To Evaluate the effectiveness of CLRT vs Manual lateral positioning in prolonged bedridden patients. 2] To Assess the effects of CLRT vs Manual lateral positioning on Blood circulation Method- This experimental comparative study, conducted over six months at Krishna Vishwa Vidyapeeth, Karad, aims to evaluate the effectiveness of Continuous Lateral Rotation Therapy (CLRT) versus manual lateral positioning in preventing and treating pressure ulcers in bedridden patients. The study will include 30 patients aged 18-50 years, randomly assigned to either Group A (CLRT on a programmable bed) or Group B (manual lateral positioning every two hours). Inclusion criteria include patients who are immobile for at least 48 hours and unable to reposition themselves, while exclusion criteria include a Glasgow Coma Scale (GCS) below 6 or increased intracranial pressure. Result-Both interventions resulted in significant improvements. The CLRT intervention led to a notable reduction in pain during activity (p=0.0033), while the MLP intervention significantly decreased pain at rest (p=0.0016). Norton Scale scores improved in both groups, with more better outcomes observed in physical condition, mental state, activity, mobility, and incontinence. Conclusion- CLRT (Continuous Lateral Rotation Therapy) and MLP (Manual Lateral Positioning) are effective strategies for preventing pressure ulcers and managing pain in bedridden patients. CLRT is particularly beneficial for improving mobility and activity tolerance, while MLP is more effective at reducing resting pain. The choice between these strategies should be based on the specific needs of the patient and the available healthcare resources.